ANALISA KEBUTUHAN AIR BERSIH PADA DI KOTA BINJAI SUMATERA UTARA - Simanjuntak, Salomo; Zai, Eben Oktavianus; Sihombing, Parto Oktavianus (Jurnal Visi Eksakta, 2020)
Human life is very dependent on the fact of good quality air which is called clean water. Clean water is one type of water-based resource that is of good quality and is commonly used by humans for consumption or in carrying out their daily activities including sanitation. The most important thing is clean water is a basic human need that affects human health. Binjai City is a city with a dense population of 283,362 people in 2020, including a small city with a usage of 100 liters / person / day. This requires an analysis of the need for clean water that can be used effectively, efficiently and sustainably. This analysis will require data: the total population obtained from the Central Bureau of Statistics and the existing clean water capacity will be obtained from PDAM Tirtasari as well as literature studies or direct links to related parties regarding the existence of clean water in the city of Binjai. The need for clean water is divided into domestic water needs and non-domestic water needs in which there are social, commercial, industrial, and government agency needs. This need will be projected until 2025 so that Binjai city needs to build a new water treatment plant.